Design And Fabrication of a Manually Operated Paver Block Making Machine. - Ddamba Timothy (Kabale University, 2023)
The paver block is one of the most important construction materials that is used mostly on construction sites. As same as bricks, paver blocks are made from a mixture of cement, sand, and water. Paver blocks are a building material intended for paving paths, sidewalks, and other similar objects with small and medium mechanical loads. For producing the best quality paver blocks, it is necessary to use a paver block machine. Most of the commercially available paver block-making machines are imported and also expensive, and the other local ones available on market are unreliable. In the proposed design, the paver block making machine will be manually operated by man without the help of the external power of an engine which makes it reliable even in times of shortage of fuel or fuel price fluctuations and can produce up to 4 paver blocks per production making it efficient. Its simple design will ensure that even the smallest construction site can easily purchase it that is at a relatively cheaper cost as compared to those that are already on market. To make the appropriate design, the required specifications will be established, components will be selected and then sized, and then a layout of the machine will be generated using 3D modeling software (DS SOLIDWORKS).